Ageing in deprivation: assessing material and social challenges among older adults in Skopje, North Macedonia - Daniel Pavlovski; Daniela Stanojkovska; Jeroen Dikken; Joost van Hoof; Hannah R. Marston (Cogent Gerontology)
As the population of North Macedonia is ageing fast, the government has a challenge to protect older people from poverty and social exclusion. This study investigates the extent of material and social deprivation experienced by older adults in the capital city of Skopje. A survey was conducted among 221 older North Macedonians to evaluate whether they can afford a set of 13 essential items that are considered important for sustaining a good quality of life. Multiple linear regression analysis was used to identify key predictors of deprivation. Cluster analysis was conducted to identify distinct profiles of deprivation. Findings show 29% of the older residents face significant deprivation, unable to afford at least five out of 13 items, 19.5% lack access to seven or more items, and 88.7% encountered at least one financial challenge, meaning 11.3% of people are able to afford all 13 items. Four clusters were identified, providing deeper insights into the socioeconomic and demographic factors. These findings indicate that older people in North Macedonia experience high levels of deprivation compared to adults in Northern and Western European countries. The study highlights the need for targeted governmental policies and strategies addressing poverty among the ageing population in North Macedonia.